Post-Tsunami Hazard: Reconstruction and Restoration - Santiago-Fandiño, Vicente (Springer, 2015)
This monograph focuses on a variety of topics related to reconstruction and restoration in post-tsunami conditions. Aspects such as coastal engineering, early warning systems and technological approaches, urban planning and settlements relocation, socio-economic redevelopment and policy, coastal ecosystems and agricultural redevelopment as well as pollution assessment are included. The reader will benefit from the various case-studies drawn from a number of countries hit by the 2004 tsunami in the Indian Ocean and the Great East Earthquake and Tsunami of March 2011 in Japan. This book will appeal to scientists and scholars, decision makers, students and practitioners interested in post-tsunami reconstruction and restoration processes.